Novel multiple images encryption algorithm using CML system and DNA encoding - Zhang, Hao; Wang, Xiao-qing; Wang, Xing-yuan; Yan, Peng-fei (IET image processing, 2020)
In this study, the authors advance a novel multiple images encryption algorithm using the coupled map lattices (CML) system and DNA encoding. The algorithm adopts a permutation-diffusion structure. First, the initial values and parameters of the CML system are determined by given values and SHA hash key of original images. Secondly, several plain images are grouped and permuted among groups. Next, different groups are combined into eight blocks of the same size, each of which is independently coded and scrambled. Thirdly, in the diffusion process, a DNA-level multiplication operation is redefined, and required key matrices are resulted from a small key connected with original images. Finally, dynamic DNA coding/decoding is adopted, and the coding and decoding rules are determined by original images. The evaluation of the simulation experiment shows that the proposed algorithm is safe and feasible, and has good encryption effect.